eCM 2006
DOI: 10.22203/ecm.v012a08
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate-enhanced chondrogenesis of ATDC5 cells

Abstract: The ATDC5 cell line exhibits the multistep chondrogenic differentiation observed during endochondral bone formation. However, it takes up to two months to complete the process of cell expansion, insulin addition to promote differentiation and further changes in culture conditions effectively to induce hypertrophy. We sought to produce consistent chondrogenesis with significant hypertrophic differentiation with simpler conditions in a more practical time period. By adding ascorbate, the prechondrogenic prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 28 publications
8
49
1
Order By: Relevance
“…Kawakami et al [64], named SOX9 as the key intracellular molecule in chondrogenesis; Bell et al [65], correlated the expression of SOX9 as a marker for expression of Col II; and Zhao et al suggested SOX9 is needed for expression of the chondrocyte phenotype. Limited literature shows SOX9 upregulated 1.25-fold [66], for hADSCs with TGF-β3 at day 28 consistent with our 1.2-fold increase at day 25, 2-fold for ATDC5 micromass with Asc at day 21 [23], consistent with the 3.9-fold increase we observed at day 25, and 2-fold for bovine BMSC micromass with Dex at day 14 [67], consistent with our 1.1-fold increase at day 14. However, the BMSC study shows no signi icant difference between Dex and DT, similar to our comparative observations between Dex and DT though both our study and the BMSC study show that addition of Dex enhances TGF-β induced SOX9 expression at day 14.…”
Section: Discussion and Future Studiessupporting
confidence: 90%
See 1 more Smart Citation
“…Kawakami et al [64], named SOX9 as the key intracellular molecule in chondrogenesis; Bell et al [65], correlated the expression of SOX9 as a marker for expression of Col II; and Zhao et al suggested SOX9 is needed for expression of the chondrocyte phenotype. Limited literature shows SOX9 upregulated 1.25-fold [66], for hADSCs with TGF-β3 at day 28 consistent with our 1.2-fold increase at day 25, 2-fold for ATDC5 micromass with Asc at day 21 [23], consistent with the 3.9-fold increase we observed at day 25, and 2-fold for bovine BMSC micromass with Dex at day 14 [67], consistent with our 1.1-fold increase at day 14. However, the BMSC study shows no signi icant difference between Dex and DT, similar to our comparative observations between Dex and DT though both our study and the BMSC study show that addition of Dex enhances TGF-β induced SOX9 expression at day 14.…”
Section: Discussion and Future Studiessupporting
confidence: 90%
“…Our Standard deviations or mRNA levels are as large and sometimes smaller than values in Acharya et al, study (two-three replicates) [51], Bruce et al, (two-six replicates) [52], and even studies with larger sample sizes of N ≥ 25 [53,54]. Such variations are also due to mixtures of differentiated and undifferentiated cells and a continuum of mRNA marker expression [23,[55][56][57]. Hence, even with large standard deviations, mean differences infer the in luence of one additive over another.…”
Section: Discussion and Future Studiesmentioning
confidence: 47%
“…The culture system used in this study has been previously described in detail [30] ATDC5 cells were cultured in a maintenance medium consisting of a 1:1 ratio of DMEM/F12 media (Cellgro, Manassas, VA) with 5% fetal bovine serum (FBS) (Hyclone, Logan, UT), 10 mg/ml human transferrin (Sigma Chemical Company, St. Louis, MO), 1% penicillin-streptomycin (Invitrogen, Carlsbad, CA), and 3 × 10 −8 M sodium selenite (Sigma). After reaching confluence, cells were cultured with differentiation media, which is identical to maintenance media with the addition of 10 mg/ml bovine insulin (Sigma) and 50 g/ml ascorbic acid (Sigma) [31,32]. At 10 days post-confluence, cells were cultured for 24 h in differentiation media supplemented with Pi (0-20 mM beyond media basal level) and 10% FBS (10% FBS was used to ensure sufficient serum proteins such as fetuin that help regulate pathologic precipitation of calcium phosphate crystals [33,34]).…”
Section: Cell Culturementioning
confidence: 99%
“…After reaching confluence cells were cultured with differentiation media, which is identical to maintenance media with the addition of 10 mg/ml bovine insulin (Sigma) and 50 mg/ml ascorbic acid (Sigma) [Atsumi et al, 1990;Altaf et al, 2006]. At 10 days post-confluence, cells were cultured for 24 h in differentiation media supplemented with Pi (0-20 mM beyond media basal level) and 10% FBS (10% FBS was used to ensure sufficient serum proteins such as fetuin that help regulate pathologic precipitation of calcium phosphate crystals [Schinke et al, 1996;Price et al, 2003]).…”
Section: à8mentioning
confidence: 99%